Factores asociados al Sindrome de Burnout en docentes de la I.E. Fe y Alegría 43 de la Salle Ventanilla - Callao - Espinoza Herrera, Natalia Isabel (Universidad Nacional Federico Villarreal, 2014)
The aim of the thesis is to relate the factors associated with burnout syndrome in teachers of School Fe and joy Salle 43 of the Ventanilla district, Callao province. the three dimensions of burnout (emotional exhaustion, depersonalization and lack of personal accomplishment) and its relation to associated factors (sex, age, marital status, economic status, emotional situation with your partner, emotional satisfaction in its associated cefactores syndrome were described (sex, age, marital status, economic status, emotional situation with your partner, emotional satisfaction in your workplace, working time in their workplace, number of students in charge, number of working hours, emotional situation with your partner , emotional satisfaction in your workplace, working time in their workplace, number of students in charge, number of working hours, situation of labor, disease and / or current illness) for this the Maslach Burnout Inventory was applied (MBI ) to a population of 35 teachers and levels of initial, primary and secondary, whose results evidence that there is no significant difference between the overall score of burnout syndrome associated factors; except for the presence of emotional exhaustion and the following associated factors (emotional satisfaction in your workplace and the presence of disease and / or current illness).

El objetivo de la tesis es relacionar los factores asociados al síndrome de burnout en docentes de la Institución Educativa Fe y alegría 43 de la Salle del distrito de ventanilla, provincia del Callao. Se describieron las tres dimensiones del síndrome de burnout (Agotamiento emocional, despersonalización y falta de realización personal) y su relación a los factores asociados (sexo, edad, estado civil, situación económica, situación afectiva con su pareja, satisfacción emocional en su cefactores asociados (sexo, edad, estado civil, situación económica, situación afectiva con su pareja, satisfacción emocional en su centro laboral, tiempo de trabajo en su centro laboral, número de alumnos a su cargo, número de horas de trabajo, situación afectiva con su pareja, satisfacción emocional en su centro laboral, tiempo de trabajo en su centro laboral, número de alumnos a su cargo, número de horas de trabajo, situación de laboral, dolencia y/o enfermedad actual) Para esto se aplicó el Maslach Burnout Inventory (MBI) a una población de 35 docentes de los niveles de inicial, primaria y secundaria; cuyos resultados obtenidos evidencia que no existe diferencia significativa entre el puntaje global del síndrome de burnout a los factores asociados; salvo la presencia del agotamiento emocional y los siguientes factores asociados ( satisfacción emocional en su centro laboral y presencia de dolencia y /o enfermedad actual).
Keywords: Factores; Asociados; Sindrome; Burnout; Docentes; Alegría; Salle; Ventanilla; Callao; https://purl.org/pe-repo/ocde/ford#5.01.00